Risk Factors of Recurrent Retinal Detachment Following Surgical Treatment for Rhegmatogenous Retinal Detachment: A Retrospective Study - Jia LY; Sun YX; Zhang YP; Ma K (Dove Medical Press, 2020)
Li-Yun Jia, Yan-Xia Sun, Yong-Peng Zhang, Kai Ma Beijing Tongren Eye Center, Beijing Tongren Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Kai MaBeijing Tongren Eye Center, Beijing Tongren Hospital, Capital Medical University, Ophthalmology and Visual Sciences Key Laboratory, Beijing 100730, People’s Republic of ChinaTel/Fax +86 1058269508Email jialiyun@126.comObjective: To identify potential risk factors for recurrent retinal detachment after surgical treatment for rhegmatogenous retinal detachment with choroidal detachment (RRD-CD) in a Chinese population.Methods: A total of 1212 patients with RRD-CD admitted to Beijing Tongren Hospital from 2004 to 2018 were reviewed retrospectively. The rate of recurrent retinal detachment was calculated, and risk factors were analyzed by logistic regression analysis.Results: The average age of the patients was 48.51 years, 760 patients (62.7%) were male, and 630 patients (52.0%) had right eye disease. The recurrence rate in the same eye was 21.3%. The incidence of recurrence retinal detachment was higher in patients who were male, middle age, and with poor preoperative vision, longer axial length, and scleral buckling. Recurrence usually occurred 3 months after surgery.Conclusion: Male, middle age, longer axial length, and scleral buckling could be risk factors for recurrent retinal detachment following surgical treatment in patients with RRD-CD.Keywords: rhegmatogenous retinal detachment, choroidal detachment, risk factor